2014
DOI: 10.1186/s12876-014-0206-x
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 Asp299Gly and Thr399Ile polymorphisms: New data and a meta-analysis

Abstract: BackgroundThe pathogenesis of inflammatory bowel disease (IBD) involves interactions between the host genetic susceptibility, intestinal microflora and mucosal immune responses through the pattern recognition receptor. Polymorphisms in toll-like receptor 4 (TLR4) induce an aberrant immune response to indigenous intestinal flora, which might favor IBD development. In this study, we aimed to determine whether TLR4 gene was associated with Crohn’s disease (CD) and ulcerative colitis (UC) among Moroccan patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
0
27
0
2
Order By: Relevance
“…Once PAMPs are recognized by leucine-rich domains, the signal cascades are initiated, and remarkable proinflammatory cytokines and chemokines, as well as costimulatory molecules, are ultimately induced through the activation of a variety of transcriptional complexes including NF-κB and AP-1 [11][12][13][14][15]. Additionally, host susceptibility to infectious diseases may be associated with the TLRs' polymorphisms [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Once PAMPs are recognized by leucine-rich domains, the signal cascades are initiated, and remarkable proinflammatory cytokines and chemokines, as well as costimulatory molecules, are ultimately induced through the activation of a variety of transcriptional complexes including NF-κB and AP-1 [11][12][13][14][15]. Additionally, host susceptibility to infectious diseases may be associated with the TLRs' polymorphisms [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al have also reported that this TLR4 polymorphism is associated with susceptibility to IBD in Caucasians . However, a previous Tunisian study failed to find any association between the allelic and genotypic TLR4 T399I polymorphism and disease susceptibility, which was replicated in another North African study including Moroccan patients with IBD . In the Tunisian population the heterogeneity in findings could be explained by the difference in patient recruitment.…”
Section: Discussionmentioning
confidence: 90%
“…TLR4 is involved in the recognition of bacterial lipopolysaccharides and in triggering innate immune responses . Two missense polymorphisms (Asp299Gly and Thr399Ile) of TLR4 gene affecting the extracellular domains of the molecule seem to cause lipopolysaccharide hypo‐responsiveness and susceptibility to develop intestinal inflammation …”
Section: Introductionmentioning
confidence: 99%
“…After the assessment of eligibility using full-text, 22 articles were excluded. Finally, 15 articles met all inclusion criteria and were included in the meta-analysis [16-20, 27-36]. Selected details of the individual studies are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Through a combination of all the available published data, it is hypothesized that a meta-analysis with increased statistical power might allow causative genes to be identified and plausible candidate genes to be excluded with reliability. Although there have been some meta-analyses focus on TLR4 polymorphism and CD, the relationship between TLR4 T399I gene polymorphism and the susceptibility to CD is controversial [20, 21]. Therefore, we conducted the present meta-analysis to quantitatively assess this relationship.…”
Section: Introductionmentioning
confidence: 99%